2008
DOI: 10.1161/atvbaha.107.158485
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Osteopontin in Recovery from Hind Limb Ischemia

Abstract: Objective-Osteopontin (OPN) is a highly phosphorylated extracellular matrix glycoprotein that is involved in a diversity of biological processes. In the vascular wall, OPN is produced by monocytes/macrophages, endothelial cells, and smooth muscle cells, and it is thought to mediate adhesion, migration, and survival of these cell types. In this study, we hypothesized that OPN plays a critical role in recovery from limb ischemia. Methods and Results-We induced hind limb ischemia in wild-type and OPN Ϫ/Ϫ mice. OP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
65
1
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 55 publications
(73 citation statements)
references
References 42 publications
5
65
1
2
Order By: Relevance
“…27 In addition, it was reported that in OPN-defective mice, fibrosis and arteriosclerotic changes were attenuated. 28,29 In this study, OPN gene transcription activity was enhanced dose-dependently and timedependently in Aldo-stimulated rVSMCs, which is consistent with reports in other various cell species, such as renal mesangium cells, 19 renal fibroblasts 21 and vascular endothelial cells. 30 As the basal levels of Aldo in the plasma of humans are around 3Â10 À10 M, a significant increase in OPN transcription starting at a concentration of 10 À9 M, as was observed in this in vitro analysis, seems to be within the clinical plasma Aldo fluctuation range.…”
Section: Discussionsupporting
confidence: 91%
“…27 In addition, it was reported that in OPN-defective mice, fibrosis and arteriosclerotic changes were attenuated. 28,29 In this study, OPN gene transcription activity was enhanced dose-dependently and timedependently in Aldo-stimulated rVSMCs, which is consistent with reports in other various cell species, such as renal mesangium cells, 19 renal fibroblasts 21 and vascular endothelial cells. 30 As the basal levels of Aldo in the plasma of humans are around 3Â10 À10 M, a significant increase in OPN transcription starting at a concentration of 10 À9 M, as was observed in this in vitro analysis, seems to be within the clinical plasma Aldo fluctuation range.…”
Section: Discussionsupporting
confidence: 91%
“…At the terminal endpoint of a longitudinal vascular remodeling study, morphological parameters such as number of collateral vessels, vessel volume, vessel thickness and connectivity may be obtained from x-ray angiography [13,15,16] or micro-CT [17,18], and high resolution capillary or arteriole density can be measured with histology by staining for CD31 or smooth muscle actin, respectively [9,[12][13][14]. Angiography and micro-CT provide a global view of the hind limb vasculature, while speckle variance OCT fills a gap in field of view between these global measurements and the two dimensional slices that are sampled with histology.…”
Section: Discussionmentioning
confidence: 99%
“…However, this technique cannot provide longitudinal data in individual animals. Similarly, xray angiography [13,15,16] and microcomputed tomography (micro-CT) [17,18] provide vessel morphology data, but are terminal endpoints that require contrast agents. Several in vivo imaging methods have also been employed to evaluate vascular remodeling over time, including fluorescence microscopy [19,20], photoacoustic microscopy [21,22], laser speckle imaging [10,23], high frequency ultrasound [24], and magnetic resonance (MR) angiography [16,25].…”
Section: Introductionmentioning
confidence: 99%
“…We therefore reduced the concentration of A-PEG-GPQ-PEG-A to 5% (vol/vol) for this study, but kept the concentrations of A-PEG-RGD and A-PEG-VEGF at 2.8 μmol∕mL and 80 μg∕mL, respectively. The left leg femoral artery of 8-9 week old strain-129 mice was ligated and excised in compliance with a well-established model of peripheral limb ischemia (24)(25)(26)(27). The right leg was left undisturbed to serve as a control reference.…”
Section: Bioartificial Matrices With Vegf Increase Rate Of Perfusion mentioning
confidence: 99%